Active learning classes in a preclinical year may help improving some soft skills of medical students - Korakrit Imwattana (2020)
© 2020 Faculty of Medicine Siriraj Hospital, Mahidol University. Objective: Active learning methods are an effective way to improve essential soft skills, such as critical thinking and social skills, and so medical educators frequently implement active learning approaches as a means to improve the soft skills of medical students. This study reports an improvement in the soft skills of medical students after the implementation of an active learning curriculum. Methods: More active learning activities were implemented in 2016 in the 3rd year medical class, involving 330 students. Overall, the number of hours devoted to active learning classes was increased from 340 hours (38.2%) in 2015 to 481 hours (59.98%) in 2016. To evaluate whether this led to any improvements in the soft skills of medical students, students undertaking the 3rd year course in the 2015 and 2016 academic years were asked to complete questionnaires to evaluate themselves (self-evaluation) as well as four other students in their same study group (peer-evaluation) at the end of the academic year. The questionnaire responses from the 2015 and the 2016 groups were compared. Results: Most students believed there was no improvement in most of the evaluated soft skills during the year. However, students in the 2016 class showed improvements in eleven outcomes in the peer-evaluation: presentation, information, technology, creativity, communication, leadership, life planning, adaptability, self-sufficiency, courtesy, and punctuality (p < 0.05). The differences were not due to the students' different background skills as the initial scores of most outcomes were identical between the two student groups (p > 0.05). Conclusion: Even without a proper design for teaching soft skills, active learning classes in a preclinical year of the medical curriculum may help improve some of the essential soft skills that medical practitioners need and, therefore, should be implemented in the medical curriculum.